Alih Aksara dan Alih Bahasa Manuskrip Teks Hikayat Nabi Ada - Sari, Amelia; Nurizzati (Persona: Kajian Bahasa dan Sastra, 2024)
This article aims to: (a) present a manuscript description of Hikayat Nabi Ada, (b) present the script translation of the teks of Hikayat Nabi Ada, (c) presents the script translation of the teks Hikayat Nabi Ada. The type of this study is philological research, this study aims to generate transcription and translation of a manuscript based on the stages and method of philological study. The focus of this are manuscripts and texts namely Hikayat Nabi Ada. This research used philological method which consisting of several stages of research. At the stage of data collection, this research used library research. After that, the stage of manuscript description, the researcher used descriptive method, then used transcription and translation method at the last stage. There are three findings of this research, that is ; (a) the form of description of the manuscript Hikayat Nabi Ada which is described based on things that have been determined in describing or identifying the manuscript; (b) the transcription of the text Hikayat Nabi Ada are from Arabic-Malay script to Latin script, the language in the text of Hikayat Nabi Ada is Malay; (c) translation of Hikayat Nabi Ada text is translated from Malay to Indonesian. The purpose of the translation is to facilitate readers who cannot understand the Malay language, so that the contents contained in the manuscript can be understood by the reader. The Hikayat Nabi Ada text tells the story of the birth of the Prophet Muhammad from the womb of his mother until marriage.